PENGARUH GAJI DAN TUNJANGAN TERHADAP KINERJA KARYAWAN YAYASAN PENDIDIKAN PONDOK PESANTREN AL-ASYÔÇÖARIYYAH BOJONEGORO - jurnalpps pps; Mukhammad Imam Muhdi; Woro Utari; Cathrine Sri Hartati (Jurnal Manajerial Bisnis, 2019)
ABSTRACT This study aims to study participation and benefits partially on employee performance and for simultaneous performance benefits for employee performance at the Al-Asy'ariyyah Bojonegoro Islamic Boarding School Education Foundation. This research includes the type of explanatory research, with research instruments in the form of questionnaires. The population in this study were all employees of the Al-asy'ariyyah Bojonegoro Islamic Boarding School Education Foundation, originating from 31 people. The sampling technique uses saturated samples, namely the entire population into a sample. The results showed that the significant variables were not significant on employee performance and significant benefits variables on employee performance. The results of the F test show that the income and allowance variables simultaneously have a significant effect on employee performance. The results of multiple linear regression test show that the regression regression coefficient has the greatest regression coefficient, so the variable allowance is the most dominant variable to improve employee performance compared to other variables. Keywords: salary, benefits, employee performance